Study on coupling coordination and collaborative optimization system of water-energy-grain - Ren, XuYan; Ren, YongTai; Pei, Wei (Frontiers in Ecology and Evolution, 2022)
In order to solve the problem that water resources in a certain province are relatively scarce and the spatial matching effect of resources is poor, which causes the w-e-f system to face the problem of trade-off, the water energy food coupling coordination and collaborative optimization system is proposed. By constructing the w-e-f multi-objective collaborative optimization model, the multi-objective optimization schemes under different weight scenarios are compared, and scenario 2 with better effect is selected as the best scheme for collaborative optimization. The results show that, on the basis of meeting the constraint conditions, by adjusting the crop planting structure and making efficient use of resource elements, the water resource consumption of major grain crops can be reduced by 7.3% and the total energy consumption can be reduced by 2.5% by 2030 compared with 2019. Conclusion: the system alleviates the problem of excessive pressure on water resources and ecological environment to a certain extent. Compared with the single objective optimization scheme, multi-objective optimization can effectively alleviate the trade-off conflict between w-e-f.